A study on factor influencing reader’s preferences toward online magazine at Kumpulan Media Karangkraf / Nadiah Syairah Mazlan - Mazlan, Nadiah Syairah (2012)
The title of this research is a factor influencing reader’s preferences toward online magazine that published by Kumpulan Media Karangkraf. The general objective for this research is to determine what the factor that contribute the reader choose online magazine as their preferences to read magazine that published by Kumpulan Media Karangkraf. The researcher intends to identify the relationship between conveniences, technology, perception and cost toward the reader’s preferences in choosing reading materials. The researcher used convenience sampling as techniques to collect 150 respondents randomly through online ways like used social networking like Facebook and Twitter and Email to complete questionnaire survey. It is because the researcher more focuses on student who are read magazine through online. The researcher use Google document as a way to distribute questionnaire. The period to collect the complete data is about one month from May until June. The data analysis techniques used in this researcher are descriptive analysis, reliability analysis, multiple regression analysis, and coefficient and correlation analysis. Based on the findings, perception factor have a relationship and significant with the reader’s preferences toward online magazine. However, convenience, technology and cost were found to be insignificant with the reader’s preferences toward online magazine. Since the online reading material is a one of the trademark or reading material use by Kumpulan Media Karangkraf, we suggest that this published company needs to create more attractive website of their magazine in order to increase the reader preferences toward online magazine